2014
DOI: 10.1002/ca.22470
|View full text |Cite
|
Sign up to set email alerts
|

Different ophthalmic artery origins: Embryology and clinical significance

Abstract: This retrospective study gives a summary of ophthalmic artery (OA) variations to serve as guidelines for surgical interventionists and trainees. Pubmed and Medline searches were conducted. The OA usually arises intradurally (superomedial, anteromedial, or rarely superolateral) from the internal carotid artery (ICA). Rare extradural origin (primitive dorsal OA) (PDOA) remnant and extremely rare interdural origin (primitive ventral OA) (PVOA) remnant are of significance when sectioning the dural ring. Rarely, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 49 publications
1
15
1
Order By: Relevance
“…According to Hayreh and Dass [ 4 ], in 83.6% of the cases it arises above dura and follows an intradural course, in 6.6% of the cases it arises just above dura, and at 10% it arises below dura and follows a totally or partially extra dural course. Other researchers [ 7 , 12 , 13 ] have published similar results. OA originates from superomedial wall of ICA in 40% of the cases, anteromedial wall in 51%, medial wall in 6%, and superior wall in only 3% of the cases [ 4 ].…”
Section: Ophthalmic Artery Originsupporting
confidence: 69%
See 2 more Smart Citations
“…According to Hayreh and Dass [ 4 ], in 83.6% of the cases it arises above dura and follows an intradural course, in 6.6% of the cases it arises just above dura, and at 10% it arises below dura and follows a totally or partially extra dural course. Other researchers [ 7 , 12 , 13 ] have published similar results. OA originates from superomedial wall of ICA in 40% of the cases, anteromedial wall in 51%, medial wall in 6%, and superior wall in only 3% of the cases [ 4 ].…”
Section: Ophthalmic Artery Originsupporting
confidence: 69%
“…OA originates from superomedial wall of ICA in 40% of the cases, anteromedial wall in 51%, medial wall in 6%, and superior wall in only 3% of the cases [ 4 ]. Those numbers are not universally accepted as other researchers have found different percentages [ 7 , 10 , 13 ].…”
Section: Ophthalmic Artery Originmentioning
confidence: 96%
See 1 more Smart Citation
“…A serious potential complication of preoperative meningioma embolization is blindness due to inadvertent central retinal artery (CRA) ischemia, caused by anomalous origin of the ophthalmic artery (OA) arising from the MMA. One study reported a 1.45% incidence of OA origin from the MMA stem or its branches, entering the orbit via the superior orbital fissure instead of the optic canal, among 1652 patients 28. This meningo-ophthalmic artery anomaly has several variants, including a single OA arising from the MMA, dual OAs with ICA and MMA origins, and the MMA arising from the OA.…”
Section: Discussionmentioning
confidence: 99%
“…The trigeminal‐cardiac reflex from the stimulation of sensory branches of the trigeminal nerve has been reported with embolization of the middle meningeal artery and may represent a direct effect of intra‐arterial injection of dimethyl sulfoxide/ethylene‐vinyl alcohol copolymer . Resolution of trigeminal neuralgia associated with arterio‐venous malformations has been reported following embolization of the middle meningeal artery at the foramen rotundum …”
Section: Discussionmentioning
confidence: 99%